Nixon's war at home: the FBI, leftist guerillas, and the origins of counterterrorism - Chard, Daniel S. (Justice, power, and politics, 2021)
The making of American counterterrorism -- Nixon, Hoover, and America's homegrown insurgency -- Off the pigs! -- Covert operations and clandestine radicals -- The Huston plan -- Improvising counterterrorism -- The war at home and the FBI's public image -- Police killing -- Deep Throat's secret wars -- Arab scare -- Implosion -- The politics of counterterrorism.